Development of Interactive Learning Multimedia Based on Android Integrated with STEM Heat Material to Improve Students' Computational Thinking - Syukron Fuad; Abdurrahman; Agus Suyatna; Dewi Lengkana (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to produce an interactive learning multimedia application product based on Android integrated with STEM heat material that is valid, practical, and effective in improving students' computational thinking skills. This research and development was carried out using a 4D model consisting of defining, designing, developing, and disseminating. This study uses a mixed methods concurrent embedded model consisting of five stages of data collection, namely qualitative data collection followed by quantitative data collection followed by providing interventions in the form of qualitative data collection followed by quantitative data collection and finally qualitative data collection. The trial design used was a non-equivalent pre-test post-test control group design. The subjects of the study were 64 junior high school students, 32 in the experimental class and 32 in the control class. The results of the study showed that the resulting product was stated as: very valid (94%) by material experts, (95%) by media experts; very practical to use in learning by students (91%), with a very high level of learning implementation, namely (94.57%); effective in improving students' computational thinking with high n-gain (0.77) and effect size with criteria of (91%). Based on the results of research and data analysis, it shows that the developed product can be used in learning heat material to improve students' computational thinking abilities.